Hate Speech and Binary Exclusions in Europe: A Digital and Communicative Approach - Galdámez Morales, Ana (The Age of Human Rights Journal, 2022)
Hate speech targeting homosexuals, transgender people and other sexual orientations, as well as gender identities that deviate from the prevailing traditional binary system pervades social networks and digital communication channels. As a result, it is causing the exclusion of these groups, which often opt for invisibility in order to survive. Freedom of expression is an essential and preferential right in Western democratic systems. Based on this premise, this paper delves into the European legal and jurisprudential framework on hate speech –especially, acts of transphobia, homophobia and violence based on sexual orientation and gender identity– as a limit to freedom of expression, when other fundamental values, such as dignity, are at stake. Based on an analysis of the main normative instruments that have attempted to define the concept, as well as recent case law on hate speech, the aim of this article is to outline a consensus and to establish stable parameters to configure a legal response –valid in the European context– to cases of homophobic or transphobic speech.